2016
DOI: 10.1158/1535-7163.mct-15-0778
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HSP90 by AUY922 Preferentially Kills Mutant KRAS Colon Cancer Cells by Activating Bim through ER Stress

Abstract: Oncogenic mutations of KRAS pose a great challenge in the treatment of colorectal cancer. Here we report that mutant KRAS colon cancer cells are nevertheless more susceptible to apoptosis induced by the HSP90 inhibitor AUY922 than those carrying wild-type KRAS. Although AUY922 inhibited HSP90 activity with comparable potency in colon cancer cells irrespective of their KRAS mutational statuses, those with mutant KRAS were markedly more sensitive to AUY922-induced apoptosis. This was associated with upregulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…We have previously shown that the HSP90 inhibitor AUY922 kills colon cancer cells through apoptosis and that wild-type KRAS colon cancer cells are more resistant to apoptosis induced by AUY922 compared with those carrying active mutations in KRAS [29]. In subsequent studies, we found that among wild-type KRAS colon cancer cells, those harbouring active mutations in BRAF were even more resistant to AUY922-induced apoptosis than cells with wild-type BRAF (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…We have previously shown that the HSP90 inhibitor AUY922 kills colon cancer cells through apoptosis and that wild-type KRAS colon cancer cells are more resistant to apoptosis induced by AUY922 compared with those carrying active mutations in KRAS [29]. In subsequent studies, we found that among wild-type KRAS colon cancer cells, those harbouring active mutations in BRAF were even more resistant to AUY922-induced apoptosis than cells with wild-type BRAF (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 77%
“…However, to our surprise, treatment with AUY922 only moderately reduced the expression of mutant BRAF while it abolished the expression of other HSP90 client proteins such as CRAF and SKP2 in mutant BRAF colon cancer cells [29]. This suggests that mutant BRAF is less dependent on HSP90 for its stabilization than other HSP90 client proteins in colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies showed that KRAS mutant colon cancer cells are more susceptible to apoptosis induced by AUY922 compared with wild-type, supporting the role of KRAS signalling in pro-apoptotic signalling functions of the HSP90 inhibitor in colon cancer cells. [25] Consistent with the pro-apoptotic effect of HSP-90 pharmacological inhibitors on colorectal cancer, Lu et al showed that LD053, an HSP90 inhibitor, upon binding to the N-terminus of HSP90, enhances dissociation of cdc37 from HSP90, leading to inhibition of pro-survival signalling pathways including c-Raf/Mek/Erk as well as PI3K/Akt in gastric cancer cells. Consistent with cellular studies, administration of LD053 inhibits growth of gastric cancer cell xenografts in nude mice.…”
Section: Gastricmentioning
confidence: 88%